2023
DOI: 10.3390/nu15112458
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Quality Index in Morbidly Obesity Patients Related to Metabolic Syndrome Markers and Cardiorespiratory Fitness

Abstract: Background: Muscle quality index (MQI) is an emerging health indicator obtained by dividing handgrip strength by body mass index (BMI) that needs to be studied in morbidly obese patients (defined by BMI ≥ 35 kg/m2). Objective: To determine the association between MQI, metabolic syndrome (MetS) markers, and cardiorespiratory fitness (CRF), and as a second objective to determine the potential mediation role of MQI in the relationship between abdominal obesity and systolic blood pressure (SBP) in this sample. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 86 publications
(98 reference statements)
1
5
0
Order By: Relevance
“…In the present investigation, there was an inverse relationship between MQI and abdominal obesity in adolescents ( p < 0.001). These results are in agreement with a recent study by Camaño-Navarrete et al [ 49 ], who showed that subjects with a low MQI had greater abdominal obesity ( p = 0.011) than the group with a high MQI. Likewise, these authors confirmed that the MQI is a partial mediator of the association between abdominal obesity and other variables, such as systolic blood pressure.…”
Section: Discussionsupporting
confidence: 93%
“…In the present investigation, there was an inverse relationship between MQI and abdominal obesity in adolescents ( p < 0.001). These results are in agreement with a recent study by Camaño-Navarrete et al [ 49 ], who showed that subjects with a low MQI had greater abdominal obesity ( p = 0.011) than the group with a high MQI. Likewise, these authors confirmed that the MQI is a partial mediator of the association between abdominal obesity and other variables, such as systolic blood pressure.…”
Section: Discussionsupporting
confidence: 93%
“…The altered muscle function in patients with cancer and chronic disease often leads to falls, disability, and functional impairment, increasing the risk of a poor outcome and death [33]. We calculated the muscle quality index (MQI) by measuring muscle strength using a handgrip dynamometer and normalizing it with either the body mass index or appendicular skeletal muscle mass index (ASMMI) [7].…”
Section: Discussionmentioning
confidence: 99%
“…Although the definition of sarcopenia varies depending on each author [38], it generally refers to the loss of skeletal muscle mass and function that occurs secondarily to factors such as chronic disease and older age. However, in patients with obesity or metabolic syndrome, for example, biochemical and molecular changes can affect the functionality of muscle fibers even if the person maintains their muscle mass, as Caamaño et al described [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations